PERAN ANALISIS FUNDAMENTAL DALAM VALUASI SAHAM DAN PENGAMBILAN KEPUTUSAN INVETASI: STUDI KASUS SAHAM BBCA PERIODE 2020-2024 - Ni Wayan Dista Anggreni; Ni Nyoman Suli Asmara Yanti (Politeknik Negeri Ambon, 2026)
Introduction: The purpose of this study is to analyze how fundamental indicators have evolved from 2020 to 2024, and how these dynamics can inform investment decisions regarding BBCA shares. Methods: This research uses a quantitative, descriptive approach, with a primary focus on analyzing the development of BBCA's fundamental stock indicators and their implications for investment decisions. Data collection was conducted through documentation, including financial reports, stock market data, and official publications related to BBCA's performance during the 2020-2024 period. Results: According to fundamental analysis, BBCA's stock valuation for the 2020-2024 period shows a relatively balanced relationship between the share price and its intrinsic value. The relative intrinsic value calculation indicates that the share price does not differ significantly from the estimated fair value. Therefore, BBCA shares can be categorized as having Fair Value. This condition indicates that investors believe BBCA's share price reflects the company's fundamental performance, taking into account both profitability and asset efficiency. So the recommended investment decision is to hold while monitoring price movements, while for prospective investors, the stock is worth considering as a long-term instrument. Keywords: BBCA, Fundamental Analysis, Stock Investment Decisions, Valuation